General Overview of Endometrial Microbiota - E. N. Goloveshkina; T. S. Skachkova; V. G. Akimkin (Фундаментальная и клиническая медицина, 2024)
Here, we aimed to summarize the current knowledge describing the endometrial microbiota. The uterine cavity was considered sterile until the second half of the 20th century. The development of molecular biology techniques such as polymerase chain reaction and sequencing enabled many studies to characterise microbial communities inside the uterine cavity. Although the average number of bacteria in the uterus is lower than in the vagina by 2-4 decimal logarithms, their diversity is still remarkable. The physiological core of endometrial microbiome has not been clearly delineated because of technical limitations including possible contamination during sampling, heterogeneity of sequencing techniques, and variations of experimental design. Bacteria might colonise the uterus from vagina, with semen, by translocation through the blood, or during the respective medical procedures. Generally, major alterations of the endometrial microbiota are triggered by gynecological diseases or assisted reproduction. Hitherto, the impact of endometrial microbiota on human health remains controversial. Understanding the relationships between the endometrial microbiota and human diseases can lead to better diagnosis, treatment and prevention of gynecological diseases. To achieve the success, future studies should employ standardized protocols, from sample collection to bioinformatics analysis.